2009
DOI: 10.5194/angeo-27-2173-2009
|View full text |Cite
|
Sign up to set email alerts
|

Radial transport of radiation belt electrons due to stormtime Pc5 waves

Abstract: Abstract. During geomagnetic storms relativistic electron fluxes in the outer radiation belt exhibit dynamic variability over multiple orders of magnitude. This requires radial transport of electrons across their drift shells and implies violation of their third adiabatic invariant. Radial transport is induced by the interaction of the electron drift motion with electric and magnetic field fluctuations in the ULF frequency range. It was previously shown that solar-wind driven ULF waves have long azimuthal wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 37 publications
0
92
0
3
Order By: Relevance
“…During such intense magnetic storms, when the ring current is intensified, storm-time Pc5 waves are observed, closely linked to quasisinusoidal disturbances at Pc5 frequencies and injections of ring current ions in the inner magnetosphere (Barfield and McPherron, 1978). Storm-time Pc5 waves can reach radial distances of up to L = 7.4 (Barfield and Lin, 1983) and break the third adiabatic invariant through drift resonance with the outer radiation belt electrons to produce rapid radial transport even as low as L = 4 (Ukhorskiy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During such intense magnetic storms, when the ring current is intensified, storm-time Pc5 waves are observed, closely linked to quasisinusoidal disturbances at Pc5 frequencies and injections of ring current ions in the inner magnetosphere (Barfield and McPherron, 1978). Storm-time Pc5 waves can reach radial distances of up to L = 7.4 (Barfield and Lin, 1983) and break the third adiabatic invariant through drift resonance with the outer radiation belt electrons to produce rapid radial transport even as low as L = 4 (Ukhorskiy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Such enhanced Pc5 wave activity penetrating deep in the magnetosphere and its effects on particle motion are linked with radial diffusion (Ukhorskiy et al, 2009;Ozeke et al, 2012Ozeke et al, , 2014. Semi-periodic variations in magnetic and electric fields steering the drift motion of trapped electrons lead to particle diffusion across drift shells from regions of lower magnetic field strength to regions of increased magnetic field strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global distribution and variability of low frequency Pc4 and Pc5 waves can be monitored by ground-based magnetometers and by satellites (Liu et al 2009), and the observed wave spectral characteristics have been used to evaluate radial diffusion coefficients (Brautigam et al 2005;Perry et al 2005;Ukhorskiy et al 2005;Huang et al 2010) and employed in dynamic modeling of the outer radiation belt (Loto'aniu et al 2006;Ukhorskiy et al 2009;Chu et al 2010). The properties of magnetospheric ULF waves, excited in response to solar wind variability, have also been obtained from global MHD simulations and used to study the dynamic variability of radiation belt electrons (Fei et al 2006;Kress et al 2007).…”
Section: Radial Transport and Acceleration By Ulf Wavesmentioning
confidence: 99%
“…Low-frequency instabilities of the ring current plasma during periods of intense geomagnetic activity are closely related with waves observed during geomagnetic storms (Ukhorskiy et al, 2009). The drift and bounce motions of energetic particles of the ring current may lead to fluctuations of electric and magnetic fields in the magnetosphere and ionosphere in the case of excess available energy (Baddeley et al, 2002).…”
Section: Introductionmentioning
confidence: 99%